Inhibitory effects of relaxin on cardiac fibroblast‐to‐myofibroblast transition: an electrophysiological study. Issue 6 (13th May 2015) - Squecco, Roberta; Sassoli, Chiara; Garella, Rachele; Chellini, Flaminia; Idrizaj, Eglantina; Nistri, Silvia; Formigli, Lucia; Bani, Daniele; Francini, Fabio
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Fibroblast‐to‐myofibroblast transition is a key mechanism in the reparative response to tissue damage, but myofibroblast persistence in the wound leads to fibrosis and organ failure. The role of relaxin as an antifibrotic agent capable of counteracting the acquisition of biophysical features of differentiated myofibroblasts deserves further investigation. What is the main finding and its importance? Electrophysiological analysis showed that relaxin, administered during profibrotic treatment, hyperpolarizes the membrane potential and attenuates delayed rectifier and inwardly rectifying K+ currents, which usually increase in the transition to myofibroblasts. These findings provide further clues to the therapeutic potential of relaxin in fibrosis. The hormone relaxin (RLX) is produced by the heart and may be involved in endogenous mechanisms of cardiac protection against ischaemic injury and fibrosis. Recent findings in cultured cardiac stromal cells suggest that RLX can inhibit fibroblast‐to‐myofibroblast transition, thereby counteracting fibrosis. In order to explore its efficiency as an antifibrotic agent further, we designed the present study to investigate whether RLX may influence the electrophysiological events associated with differentiation of cardiac stromal cells to myofibroblasts. Primary cardiac proto‐myofibroblasts and NIH/3T3 fibroblasts were induced to myofibroblasts by transforming growth factor‐β1, and the electrophysiological features of both cell populations were investigated by whole‐cell patch clamp. We demonstrated that proto‐myofibroblasts and myofibroblasts express different membrane passive properties and K+ currents. Here, we have shown, for the first time, that RLX (100 ng ml−1) significantly reduced both voltage‐ and Ca2+‐dependent delayed‐rectifier and inward‐rectifying K+ currents that are typically increased in myofibroblasts compared with proto‐myofibroblasts, suggesting that this hormone can antagonize the biophysical effects of transforming growth factor‐β1 in inducing myofibroblast differentiation. These newly recognized effects of RLX on the electrical properties of cardiac stromal cell membrane correlate well with its well‐known ability to suppress myofibroblast differentiation, further supporting the possibility that RLX may be used for the treatment of cardiac fibrosis.